Mass Communication: Building Community Empowerment Through Instagram @karangtaruna_sewet - Mohamad Rafly Nur Ashefi; Sri Wulandari; Dian Andriany (CV. Media Digital Publikasi Indonesia, 2026)
This study aims to analyze the role of mass communication in community empowerment through the Instagram account @karangtaruna_sewet as a means of disseminating community development innovations. The rapid development of information technology has changed the patterns of interaction and information sharing among communities, making social media platforms such as Instagram an effective instrument of mass communication. Karang Taruna, as a youth organization, faces challenges in communicating innovative ideas and increasing community participation. This study examines the effectiveness of using the Instagram account @karangtaruna_sewet in supporting the community empowerment process. Using Everett M. Rogers' (1983) Innovation Diffusion Theory, this study analyzes how Karang Taruna's innovative programs are disseminated and adopted by the community through the Instagram platform. The research method used is qualitative with a literature study approach for data collection and analysis. The results show that Instagram plays a significant role in every stage of the innovation diffusion process, including: knowledge, persuasion, decision, implementation, and confirmation. Optimizing Instagram features, using communicative language, and emphasizing the concrete benefits of the program proved effective in encouraging innovation adoption. This study contributes to the understanding of the application of innovation diffusion theory in the digital era and the effectiveness of social media as a strategic instrument in sustainable community development.